1999
DOI: 10.20870/oeno-one.1999.33.3.1022
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal (Pb, Cu, Zn and Cd) content in wine produced from grape cultivar Mavrud, grown in an industrially polluted region

Abstract: <p style="text-align: justify;">The investigation was carried out in the period 1991-1993 with cv. Mavrud, grown in the region with a major industrial pollutant the Non-Ferrous-Metal Works (NFMW) and a region with no industrial pollutants (as a control). The heavy metal content in soil, grapes and wine was determined. Most of the heavy metals in the grapes precipitate during fermentation into the sediments, which is the reason for their significantly lower content in the wine. Water washing of grape befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
(7 reference statements)
2
6
0
Order By: Relevance
“…For toxic elements, As, Cd, and Pb were generally significantly higher for Vineyards 2, 3, and 4 than Vineyards 1 and 5 ( Table 4 ). Leaf Ca, K, Mg, Fe, Mn, Cr, and Zn concentrations in our study were comparable with values reported by Angelova et al [ 35 ], Chopin et al [ 24 ], Cugnetto et al [ 7 ], Milićević et al [ 29 ], Vystavna et al [ 36 ], and Vystavna et al [ 37 ].…”
Section: Resultssupporting
confidence: 91%
“…For toxic elements, As, Cd, and Pb were generally significantly higher for Vineyards 2, 3, and 4 than Vineyards 1 and 5 ( Table 4 ). Leaf Ca, K, Mg, Fe, Mn, Cr, and Zn concentrations in our study were comparable with values reported by Angelova et al [ 35 ], Chopin et al [ 24 ], Cugnetto et al [ 7 ], Milićević et al [ 29 ], Vystavna et al [ 36 ], and Vystavna et al [ 37 ].…”
Section: Resultssupporting
confidence: 91%
“…As concentrations up to 1000 mg copper sulphate per kg soil can still be found in some places (Flores-Vélez et al 1996 ) and surface layer of soil poses the highest level of copper as reported by Angelova et al ( 1999 ) isolation of Pseudomonas strains at this depth (5 cm) hereby corresponds to the copper resistance traits. Therefore, anthropogenic accumulation of copper likely explains the prevalence of Pseudomonas that could support the growth of plants treated with copper sulphate over the years in order to control fungal diseases.…”
Section: Discussionmentioning
confidence: 60%
“…The limit set by the European Union for iron in the wine is less than 30 mg/L, or according to the International Organisation of Vine and Wine (OIV) less than 10 mg/L. Most of the heavy metals in the grapes precipitate during fermentation into the sediments, which is the reason for their significantly lower content in the wine [8]. The application of fining agents, such as bentonite, copper sulfate (Al, Ca, Cd, Cr, Cu, Fe, Zn) and other environmental pollution (Cd, Co, Cr, Hg, Ni, Pb, V) may contribute also to wine contamination [9].…”
Section: -Results and Discussionmentioning
confidence: 99%